Inventarisasi Dendrobium linearifolium Teijsm. & Binn. Dan Pohon Inangnya Di Kawasan Desa Lemukih, Buleleng - Bali - Ni Made Gari; Junita Hardini; I Ketut Ginantra (Bumi Lestari Journal of Environment, 2022)
Dendrobium linearifolium Teijsm. & Binn. or "shrimp orchid" is one of the epiphytic orchids that is increasingly rare, therefore ex situ conservation is necessary. The success of ex situ orchid conservation requires knowing the types of its host trees. The study aimed to carry out an inventory of D. linearifolium and its host trees in the Lemukih Village Area, Buleleng – Bali. An explorative method was applied in the research. There were 63 individuals of D. linearifolium found in Lemukih Village. The highest number was present at an altitude of 500-700 meters above sea level (masl) (35), followed by those at 901-1200 m apl (22) and at 701-900 m apl (6) respectively. Meanwhile, 17 host trees were obtained which consisted of 10 species and eight families. Most D. linearifolium were found on Syzygium aqueum (Burm.f.) Alston (11), followed by those on Tamarindus indica L. (10), Helicia robusta (Roxb) R.Br. ex Blume (10) and Coffea canephora L. (7).